Populations reléguées et projets paysagers dans les marges de l’agglomération parisienne. Le cas de la plaine de Pierrelaye - Morgane Flégeau (EchoGéo)
The recent interest of public stakeholders towards wastelands in the central part of the Paris region appears also clearly in its margins. We would like to study a landscape project in the Pierrelaye’s plain. The project aims to transform this wasteland, that is today a polluted area, into a forest. Mainly composed by unexploited agricultural lands, this space is also occupied by families from the Travelling Community and Roma population. The travelers are altogether accused of being responsible for the decline of this space and of being an issue for the implementation of the project. We will focus on how the project realization is leaving them out and how the land regulation is established for the sake of the project and not according to the law.